Analyse de l’effet L1 dans l’émergence de l’auxiliation en français L2 - Cyrille Granget (Discours)
The purpose of this study is to understand the influence of the first language (L1) on the emergence of auxiliary verbal constructions (AVCs) in a second language (L2). In particular, we investigate the influence of Japanese L1 on the use of AVCs in French L2. A first study analyzed and compared the use of AVCs in French L2 narratives produced by 7 Japanese speakers and by a group of 7 speakers with a different L1, German, at the same level of proficiency. The contrastive analysis of verbal forms used in plural contexts revealed a clear tendency for Japanese speakers of French L2 to use AVCs. The second study aimed at, first, verifying the overuse of AVCs in Japanese learners of French by analyzing four retellings from another corpus of French L2 retellings. Second, it tested two hypotheses on the emergence of AVCs in the French L2 used by Japanese speakers. The discourse hypothesis stipulates that information structure and temporal anchoring of the discourse trigger the use of auxiliary verbs to maintain reference to number and adopt the L1 conceptualization of events. The prosodic hypothesis proposes that the auxiliary in French L2 is initially an epenthetical vowel due to the syllabification of French L2 influenced by the phonological and prosodic structure of Japanese. Overall, this investigation shows the influence of the L1 and underlines the benefits of considering more than one hypothesis to analyze the emergence of auxiliary constructions in an L2.